PENERAPAN DIGITAL MARKETING SEBAGAI UPAYA UNTUK MENINGKATKAN PENDAPATAN UMKM: STUDI KASUS PEMASARAN KAIN TENUN DI DESA PRINGGASELA - Haq, Habil; Nurlaili, Nurlaili; Sari, Adinda Kumala; Yuhinis, Baiq Ilil; Iqbal, Iqbal; Wicaksana, M. Arman Adhi; Febrianti, Ni Luh Riska; Moerad, Siti Huwayda; Prajasa, Syakira Mala; Ngudiyono, Ngudiyono (Universitas Mataram, 2024)
Pringgasela is one of the villages in East Lombok regency that has strength in the development of MSMEs (micro, small and Medium Enterprises). One of the mainstay business sectors in Pringgasela Village is weaving, various activities have been carried out to identify and provide solutions to existing problems, activities begin with observations and interviews with local people, especially weaving cloth craftsmen and MSME actors. The identification results show that although Pringgasela village has great potential in MSMEs, especially in the production of woven fabrics, there are significant constraints in market access, caused by the lack of utilization of digital media. In response to these problems, the solution implemented is to organize socialization and training focused on improving the use of digital media as a marketing method. It is expected that the program can increase the income and welfare of the community, especially MSME actors. This Program shows that the use of digital technology can be an effective solution in overcoming economic challenges in the village, as well as strengthening existing local potential.